Karakteristik Ulkus Diabetikum RSUD Cut Meutia Kabupaten Aceh Utara - Ilhami Zalianty; Maulina Debbyousha; Zubir Zubir (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by inadequate insulin production or the development of insulin resistance, resulting in persistent hyperglycemia. One of the common complications of diabetes mellitus is diabetic ulcer, which develops due to microangiopathy and macroangiopathy that impair blood circulation and tissue healing. Diabetic ulcers can significantly reduce patients’ quality of life and increase the risk of infection, hospitalization, and amputation if not managed properly. This study aimed to identify, describe, and evaluate the characteristics of diabetic ulcers among patients treated at Cut Meutia Regional General Hospital, North Aceh Regency. The study employed a descriptive observational design with a cross-sectional approach involving 50 respondents selected through purposive sampling. Data were collected from patient records and observations of ulcer characteristics. The findings showed that most respondents (34%) had Meggitt-Wagner grade 1 diabetic ulcers. The majority of participants were male (58%) and aged between 45–59 years (66%). Half of the respondents had experienced diabetes mellitus for less than five years before ulcer development (50%). Regarding nutritional status, most respondents had a normal body mass index (30%). All respondents had uncontrolled HbA1c levels (100%), indicating poor glycemic control, while more than half reported a history of smoking (54%). These findings highlight the importance of glycemic control, smoking cessation, and regular foot care in preventing diabetic ulcers and reducing the risk of further complications among patients with diabetes mellitus.